A Work study on Chairman Garments, Inc. - Go, Michelle Christine (College of Engineering, 1998)
The group studied the production processes in the Chairman Garments Company. They used the techniques in method study in finding out the problem areas in their production line. There were three major problems listed by the group : 1) there was no standard output in the company, 2) improper lay-out and 3) improper scheduling by management. These problems led to the delay of products and also reduced the company's operating income. The group analyzed each problem and their effects. The group used the techniques studied in IE 32 and then recommended the following conclusions : to change the lay -out of the factory and then determine a standard output for the employees.